Enlarging the concept of sustainable nutrition: Nutritional and environmental aspects (Research, Society and Development, 2022)
The concept of sustainable nutrition is related to the way we treat both the environment and the health of humans, being a reflection of the way we use natural resources. This study had as its main objective to understand how sustainable nutrition generates nutritional and environmental impact. It turns out that it is an integrative literature review study, addressing the theme. The bibliographic searches were made through the periodical databases CAPES, MEDLINE, SCIELO, using the Decs (health science descriptors), involving review articles, monographs, and books. At the end of the search, meeting the criteria for inclusion and exclusion of articles, the 17 most relevant papers were analyzed. It was found that sustainable nutrition seeks to reduce greenhouse gas emissions, soil erosion, energy and water use in the food production chain, and to increase biodiversity and the amount of vitamins, minerals, and phytochemicals. Overall, the authors studied agree that a diet with low environmental impact is generally consistent with good nutrition. The most sustainable diets would contain a high proportion of plants and a low proportion of animals, and would be extremely heterogeneous.